Will You Protect Me or Make the Situation Worse?: Teachers’ Responses to School Violence Against Students With Disabilities - Njelesani, Janet (Journal of interpersonal violence, 2022)
School violence is a global public health epidemic, with students with disabilities at a significantly greater risk than their non-disabled peers. Students with disabilities are more vulnerable to school violence from peers, teachers, and school staff due to stereotypes and prejudice. Teachers are pivotal in preventing violence and intervening, but literature on the role that teachers play in responding to disability-based violence is limited. Guided by the social?ecological framework of bullying, this qualitative study explored educators? responses to school violence against students with disabilities in Zambia. Data generation included document review, interviews, and focus groups with 33 teachers and 12 parents, and child-friendly methods with 90 students with disabilities. Findings illuminated that students with disabilities are less safe in schools. Teachers are not responding to violence seen or heard about due to stigmatizing beliefs and cultural norms surrounding disability and violence, with students with disabilities blamed for the violence and the response being their burden. Students with disabilities felt protected by special education teachers; however, disability-based stigma did not end with the student. By association, special education teachers were experiencing stigma from other teachers and were discouraged to respond. This stigma undermined the support special education teachers could provide to decrease school violence. Findings provide direction so teachers can respond to school violence in prosocial ways that create an environment where students with disabilities feel safe.